2020
DOI: 10.1038/s41419-020-2593-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of adenosine A3 receptor protects retinal ganglion cells from degeneration induced by ocular hypertension

Abstract: Glaucoma is a progressive chronic retinal degenerative disease and a leading cause of global irreversible blindness. This disease is characterized by optic nerve damage and retinal ganglion cell (RGC) death. The current treatments available target the lowering of intraocular pressure (IOP), the main risk factor for disease onset and development. However, in some patients, vision loss progresses despite successful IOP control, indicating that new and effective treatments are needed, such as those targeting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
(75 reference statements)
1
14
0
Order By: Relevance
“…This is an in vitro study in which the contribution of other cells is not considered, but future studies evaluating whether A 3 R agonists can control microglia-mediated neuroinflammation in an animal model of ocular hypertension will help clarifying the potential anti-inflammatory effects of A 3 R activation. Taken these results showing that 2-Cl-IB-MECA reduces pro-inflammatory microglia responses elicited by elevated pressure and our previous reports [ 23 , 24 ], one may envisage that A 3 R activation may have protective properties to RGCs in glaucomatous conditions, not only by triggering survival mechanisms directly on A 3 R-expressing RGCs, but also by controlling microglia reactivity.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This is an in vitro study in which the contribution of other cells is not considered, but future studies evaluating whether A 3 R agonists can control microglia-mediated neuroinflammation in an animal model of ocular hypertension will help clarifying the potential anti-inflammatory effects of A 3 R activation. Taken these results showing that 2-Cl-IB-MECA reduces pro-inflammatory microglia responses elicited by elevated pressure and our previous reports [ 23 , 24 ], one may envisage that A 3 R activation may have protective properties to RGCs in glaucomatous conditions, not only by triggering survival mechanisms directly on A 3 R-expressing RGCs, but also by controlling microglia reactivity.…”
Section: Discussionsupporting
confidence: 85%
“…The A 3 R is expressed in RGCs [ 22 ] and the agonist 2-Cl-IB-MECA promotes neurite development in cultured RGCs and axon regeneration in an animal model of optic nerve crush [ 25 ]. Recently, we identified A 3 R as a molecular target with therapeutic potential to protect RGCs [ 23 ]. Moreover, we showed that the activation of the A 3 R is neuroprotective to retinal cells, including RGCs, from excitotoxic insults [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations